A Clinical Calculator of Conditional Survival Estimates for Resected and Unresected Pancreatic Cancer Survivors - Katz, Matthew HG (2012)
BACKGROUND: Standard estimates of survival do not reflect temporal changes in risk and are applicable only at the initial diagnosis of cancer. Conditional survival estimates provide more accurate prognostic information for cancer survivors. We sought to calculate conditional survival estimates for patients with pancreatic adenocarcinoma. STUDY DESIGN: We identified patients with pancreatic adenocarcinoma diagnosed between 1988 and 2005 in the Surveillance Epidemiology End Results (SEER) cancer registry. We constructed separate multivariate survival models, adjusted for seven clinicopathologic factors, for patients who did and did not undergo radical surgical resection. RESULTS: Conditional survival probabilities increased over time for all patients with pancreatic cancer regardless of patient characteristics, disease stage, or treatment. For patients with resected stage I, II and III disease, 3-year conditional cancer-specific survival increased from 38% to 70%, 19% to 54%, and 8% to 39%, respectively, over the three years following diagnosis. The relative improvement in survival over time was larger for patients with advanced disease. A customizable, internet browser-based clinical calculator was implemented that may be used to compute, in real time, personalized conditional survival estimates based on an individual’s unique clinicopathologic profile. CONCLUSIONS: Conditional survival estimates provide a more accurate—and typically more optimistic—assessment of prognosis for patients with pancreatic cancer than do traditional survival estimates that apply only at the initial diagnosis.